Sex differences in obesity and cognitive function in a cognitively normal aging Chinese Han population - Li, Wei (Neuropsychiatr Dis Treat, 2017)
BACKGROUND: Sex differences in Alzheimer’s disease and mild cognitive impairment have been well recognized. However, sex differences in cognitive function and obesity in cognitively normal aging Chinese Han population have not attracted much attention. OBJECTIVE: The aim of this study was to investigate the relationship between sex, obesity, and cognitive function in an elderly Chinese population with normal cognitive function. SUBJECTS AND METHODS: A total of 228 cognitively normal aging participants (males/females =93/135) entered this study. Their general demographic information (sex, age, and education) was collected by standardized questionnaire. Apolipoprotein E (APOE) genotype and serum lipid levels were measured. The Montreal Cognitive Assessment (MoCA) was used to assess participants’ cognitive function. RESULTS: The prevalence of obesity in elderly women (18/133, 13.5%) was significantly higher than that in men (5/92, 5.4%, P=0.009). Regression analyses showed that obesity was associated with drinking alcohol (OR =13.695, P=0.045) and triglyceride (OR =1.436, P=0.048) in women and limited to low-density lipoprotein (OR =11.829, P=0.023) in men. Women performed worse on the naming score for MoCA than men (P<0.01). Stepwise linear regression analysis showed that education (t=3.689, P<0.001) and smoking (t=2.031, P=0.045) were related to the score of naming in female, while high-density lipoprotein (t=−2.077, P=0.041) was related to the score of naming in male; however, no correlation was found between body mass index and cognitive function in both male and female (P>0.05). CONCLUSION: Our finding suggests that there are significant sex differences in obesity and specific cognitive domains in aging Chinese Han population with normal cognitive function.